Click Chemistry as a Convenient Tool for the Incorporation of a Ruthenium Chromophore and a Nickel–Salen Monomer into a Visible‐Light‐Active Assembly. Issue 4 (4th December 2012) - Herrero, Christian; Batchelor, Luke; Baron, Aurélie; El Ghachtouli, Sanae; Sheth, Sujitraj; Guillot, Régis; Vauzeilles, Boris; Sircoglou, Marie; Mallah, Talal; Leibl, Winfried; Aukauloo, Ally
Abstract: Click chemistry was used to assemble a trimetallic Ru II –Ni II –Ru II complex made up of two tris(bipyridyl)ruthenium(II)‐based photosensitisers and a nickel(II)–salen complex. The electrochemical and photophysical properties of the resulting photosensitiser–metal complex are discussed. Photoinduced activation triggered by visible light absorption induces a fast intramolecular charge shift from one of the chromophores to the salen cavity to generate a nickel(III)–salen species. Abstract : Click chemistry led to the rapid synthesis of a photosensitiser–metal complex. Under visible light excitation, and in the presence of an electron acceptor, intramolecular photoinduced electron transfer was triggered to oxidise the nickel(II) ion lodged in the salen moiety.